Discutindo sobre o fracasso escolar na perspectiva de Bernard Charlot: em foco uma escola pública paulista de educação básica - Renato Bellotti Senicato; Cláudia Beatriz de Castro Nascimento Ometto (Universidade Estadual de Campinas, 2014)
This article is the result of a research project funded by CNPq / CAPES period of 2013-2014, developed in a school serving students from elementary education II and high school. The project aims to understand aspects of the training of readers and writers in the elementary school, since it is concerned with the admission of students not literate in the sixth year. As part of the wider project developed a research project to understand how Bernard Charlot comprises a school, place of training of young people, since for him is in relation with the knowledge that ubjects participating in different modes of the process social reproduction signifying their school experience and transforming itself. Methodologically, the Lessons Collective Pedagogical Work with teachers and classes that involved working with reading and writing were audio recorded during the year 2013 so they could be analyzed. We also take as material for analysis electronic correspondence exchanged between teachers and researchers, as well as the materials posted on social networks of which we were part. In this paper, we question the subtle interface between assessments and large-scale production of school failure relating it to media fanfare. Points to resistance from educators to current accountability policies in education, which cross the pedagogical work "tying" the curriculum does not always mean a certain school communities to certain contents. It is noteworthy, in this process, the importance of collective work in lieu of the prescriptive official determinations.